What Are the Proteolytic Enzymes of Honey and What They Do Tell Us? A Fingerprint Analysis by 2-D Zymography of Unifloral Honeys - Rossano, Rocco; Larocca, Marilena; Polito, Teresa; Perna, Anna Maria; Padula, Maria Carmela; Martelli, Giuseppe; Riccio, Paolo (PLOS ONE, 2012)
Honey is a sweet and healthy food produced by honeybees (Apis mellifera L.) from flower nectars. Using bidimensional zymography, we have detected the, until now unrevealed, proteolytic activities present in row honey samples. The resulting zymograms were specific for each type of the four unifloral honey under study, and enzymes were identified as serine proteases by the use of specific inhibitors. Further, using bidimensional electrophoresis, we have shown that honey proteases are able to degrade the major Royal Jelly proteins and in particular MRPJ-1, the protein that promotes queen differentiation in honeybees. Our findings open new perspectives for the better understanding of honeybee development, social behaviour and role in honey production. The now discovered honey proteases may influence honey properties and quality, and bidimensional zymograms might be useful to distinguish between different honey types, establish their age and floral origin, and allow honey certification.